Analysis of Genetic Association Between ABCA7 Polymorphism and Alzheimer’s Disease Risk in the Southern Chinese Population - Wang, Lijun; Jiao, Yang; Zhao, Aonan; Xu, Xiaomeng; Ye, Guanyu; Zhang, Yichi; Wang, Ying; Deng, Yulei; Xu, Wei; Liu, Jun (Frontiers in Aging Neuroscience, 2022)
Objective The study aimed to clarify the association of the 21 single nucleotide polymorphisms (SNPs) with Alzheimer’s disease (AD) in the population of southern China. Methods A case-control study was conducted with a total sample size of 490 subjects (246 patients with AD and 244 age- and gender-matched healthy controls) enrolled in this study. Twenty-one selected SNPs were detected using SNaPshot assay and polymerase chain reaction (PCR) technique. Then, we assessed how these SNPs correlated with AD susceptibility. Results The results showed that rs3764650 of ABCA7 was closely correlated with risen AD morbidity in the allele [P = 0.010, odds ratio (OR) = 1.43, 95% confidence interval (CI) 1.09–1.89], dominant (P = 0.004, OR = 1.71, 95% CI 1.19–2.46), and additive (P = 0.012, OR = 1.42, 95% CI 1.08–1.86) models. However, rs4147929 of ABCA7 was related to higher AD risk in the allele (P = 0.006, OR = 1.45, 95% CI 1.11–1.89), dominant (P = 0.012, OR = 1.59, 95% CI 1.11–2.27), and additive (P = 0.010, OR = 1.40, 95% CI 1.08–1.81) models. In addition, the frequencies of the G-allele at rs3764650 (P = 0.030) and the A-allele at rs4147929 (P = 0.001) in AD were statistically higher in APOE ε4 carriers in comparison to non-carriers. Conclusion This study demonstrated that the G-allele at rs3764650 and the A-allele at rs4147929 appeared at higher risk for developing AD, particularly in APOE ε4 carriers. Moreover, it was observed that rs3764650 and rs4147929 of ABCA7 were linked to AD. More in-depth research with a relatively large sample is needed to make the results more convincing.